National Stereotyping, Identity Politics, European Crises (Volume 27) - Leerssen, Joep; Barkhoff, Jürgen (Brill, 2021)
The articulation of collective identity by means of a stereotyped repertoire of exclusionary characterizations of Self and Other is one of the longest-standing literary traditions in Europe and as such has become part of a global modernity. Recently, this discourse of Othering and national stereotyping has gained fresh political virulence as a result of the rise of "Identity Politics". What is more, this newly politicized self/other discourse has affected Europe itself as that continent has been weathering a series of economic and political crises in recent years. The present volume traces the conjunction between cultural and literary traditions and contemporary ideologies during the crisis of European multilateralism. Contributors: Aelita Ambrulevičiūtė, Jürgen Barkhoff, Stefan Berger, Zrinka Blažević, Daniel Carey, Ana María Fraile, Wulf Kansteiner, Joep Leerssen, Hercules Millas, Zenonas Norkus, Aidan O'Malley, Raúl Sánchez Prieto, Karel Šima, Luc Van Doorslaer,Ruth Wodak